2020
DOI: 10.1038/s42004-020-00392-z
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of protonated R-homocitrate in extracted FeMo-cofactor of nitrogenase via vibrational circular dichroism spectroscopy

Abstract: Protonation of FeMo-cofactor (FeMo-co) is important for the process of substrate hydrogenation. Its structure has been clarified as Δ-Mo*Fe7S9C(R-homocit*)(cys)(Hhis) after the efforts of nearly 30 years, but it remains controversial whether FeMo-co is protonated or deprotonated with chelated ≡C − O(H) homocitrate. We have used protonated molybdenum(V) lactate 1 and its enantiomer as model compounds for R-homocitrate in FeMo-co of nitrogenase. Vibrational circular dichroism (VCD) spectrum of 1 at 1051 cm−1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…Refering to the new strategy of opposite action and that tartrates should be aerobic, they have good affinities for non-nitrogenous CO 2 and O 2 , while they repel N 2 , CH 4 , or H 2 . 35,36 These also show the same adsorption performances as similar molybdenum complexes like (4-Hmim 17,37 In summary, CO 2 adsorption curves all satisfied the famous Type-I Langmuir adsorption isotherms: 38 the amounts of gas adsorptions increase as the pressure increases and are then maintained. That is, the adsorption value will reach a maximum 13.89 mg g −1 at 29.9 bar for D-1, 15.09 mg g −1 at 29.9 bar for L-1, 2.69 mg g −1 at 23.9 bar for D-2, and 3.35 mg g −1 at 21.9 bar for L-2, respectively.…”
Section: Gas Adsorption Propertiesmentioning
confidence: 64%
See 3 more Smart Citations
“…Refering to the new strategy of opposite action and that tartrates should be aerobic, they have good affinities for non-nitrogenous CO 2 and O 2 , while they repel N 2 , CH 4 , or H 2 . 35,36 These also show the same adsorption performances as similar molybdenum complexes like (4-Hmim 17,37 In summary, CO 2 adsorption curves all satisfied the famous Type-I Langmuir adsorption isotherms: 38 the amounts of gas adsorptions increase as the pressure increases and are then maintained. That is, the adsorption value will reach a maximum 13.89 mg g −1 at 29.9 bar for D-1, 15.09 mg g −1 at 29.9 bar for L-1, 2.69 mg g −1 at 23.9 bar for D-2, and 3.35 mg g −1 at 21.9 bar for L-2, respectively.…”
Section: Gas Adsorption Propertiesmentioning
confidence: 64%
“…Comparing the pure gas adsorptions in Figure , we can see that microporous materials 1 and 2 are all able to attach some O 2 and CO 2 , while they do not respond to CH 4 , H 2 , or N 2 at 298 K. This can be attributed to the specific structures in 1 and 2 , which are mainly composed of α-hydroxycarboxylates and multi-N Htrz and H2-mim molecules. Refering to the new strategy of opposite action and that tartrates should be aerobic, they have good affinities for non-nitrogenous CO 2 and O 2 , while they repel N 2 , CH 4 , or H 2 . , These also show the same adsorption performances as similar molybdenum complexes like (4-Hmim) 6 [Mo 3 (μ 3 -S)­(μ 2 -O) 3 (glyc) 3 (4-mim) 3 ] 2 [MoO 2 (glyc) 2 ] (H 2 glyc = glycolic acid, 4-mim = 4-methylimidazole) and [Mo 2 O 2 (μ 2 -S)­(μ 2 -O)­( l -Hlact) 2 (Htrz) 2 (Htrz)] (H 2 lact = lactic acid) reported previously. , In summary, CO 2 adsorption curves all satisfied the famous Type-I Langmuir adsorption isotherms: the amounts of gas adsorptions increase as the pressure increases and are then maintained. That is, the adsorption value will reach a maximum 13.89 mg g –1 at 29.9 bar for d - 1 , 15.09 mg g –1 at 29.9 bar for l - 1 , 2.69 mg g –1 at 23.9 bar for d - 2 , and 3.35 mg g –1 at 21.9 bar for l - 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In particular, N 2 -bound and protonated structures and redox states of the cofactors in nitrogenases are important for understanding the reaction mechanism in the bio-reduction chemical process. 3,4 With the combinations of protein structures [5][6][7] and spectroscopic studies, 8,9 the structure of FeMo-co has been revealed as MoFe 7 S 9 C(cys)(Hhis)(R-Hhomocit) (H 4 homocit = homocitric acid, C 7 H 10 O 7 , Hcys = cysteine, C 3 H 7 NO 2 S, Hhis = histidine, C 6 H 9 N 3 O 2 ).…”
Section: Introductionmentioning
confidence: 99%